If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -5i)(5 + 5i) = 0 Multiply (5 + -5i) * (5 + 5i) (5(5 + 5i) + -5i * (5 + 5i)) = 0 ((5 * 5 + 5i * 5) + -5i * (5 + 5i)) = 0 ((25 + 25i) + -5i * (5 + 5i)) = 0 (25 + 25i + (5 * -5i + 5i * -5i)) = 0 (25 + 25i + (-25i + -25i2)) = 0 Combine like terms: 25i + -25i = 0 (25 + 0 + -25i2) = 0 (25 + -25i2) = 0 Solving 25 + -25i2 = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -25i2 = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -25i2 = 0 + -25 -25i2 = 0 + -25 Combine like terms: 0 + -25 = -25 -25i2 = -25 Divide each side by '-25'. i2 = 1 Simplifying i2 = 1 Take the square root of each side: i = {-1, 1}
| .644-28.98x+318x^2=0 | | 6(x-3)=-6x+90 | | 6(x-3)=6x+90 | | P+14=34 | | 5-(x+3)=12 | | K*8+42-18+E*15=X | | 4*d-5=-d | | 2x-6+5x=8 | | 2-5*h+3=-28 | | X+7=3+4 | | 2x-7+4=11 | | 11x=77 | | X^2+14x+55=0 | | 4(-2)z+8(-2)+3+(-2)+6= | | 4x+3-2x=28 | | 18=6t | | 14-3x=47 | | -2x+-6+1=-7 | | 5-7x=-16 | | 5x+41=105-3x | | 4u^2-28u-72= | | 591x=3 | | -8x-2y=0 | | 0.5-(0.3x-0.6)=-1.5 | | y=-160-9(-9) | | -18+5x=-12+-1 | | x-8+x=2x-1 | | y=-160-9(x) | | -3x-2=3x-5+8 | | 4x^2-19x+35=2x+8 | | 5x=x+24 | | -2k+k-3k=7+2k-2 |